Lee Kuan Yew : the ‘engine’ that was ‘too big for the boat’ - Kumar Ramakrishna (2015)
Former Prime Minister Lee Kuan Yew’s renowned intellectual, moral and political strengths played a major role in Singapore’s rise from Third World to First in one generation. Fair-minded Singaporeans are unlikely to forget his achievements.